Volcano monitoring and geomatics detection methods: Mount Melbourne Fumarolic Ice Cave surveying - Migliorini, Alessandro (Alma Mater Studiorum - Università di Bologna, 2024)
The aim of this thesis is to conduct a scientific research on some peculiar phenomena that embrace multiple fields of study and are of interest to a vast public. The subject of this investigation is the active volcano called Mount Melbourne, or rather the analysis of some of its specific elements, which are the subject of direct field studies and surveys performed by researchers taking part in the Italian missions in Antarctica, the continent where the volcano is located. Mount Melbourne represents an exceptional environment in which to conduct scientific research, not only in terms of the volcanic phenomena observed in a glacial environment, but also because of the endless possibilities of applying survey methods of the most diverse kinds in environments that do not allow for normal working methods. The final goal of the thesis, hence, is to contribute to the general understanding of the volcanic activities on mount Melbourne trough the analysis of a portion of the summit caldera and a Fumarolic Ice Cave beneath it which are the main sites detected.